Relationship between Student Perception on Self-achievements and Attitudes toward Statistics: A Spearman’s Correlation Analysis - Zaini, Bahtiar Jamili; Mansor, Rosnalini; Md Yusof, Zahayu (Brnss Publication Hub, 2018)
Students’ perception on statistics is an important element in making sure that they love or do not love the subject. When students interested in learning statistics, their performance in that subject will be good and vice versa. In this study, the relationship between students’ perception on their self-achievement in mathematics and their attitude toward elementary statistics course was investigated. The respondents were selected from different courses, ethnic and religious background, gender, and age group. Sample respondents of 274 were chosen from 18 different classes for elementary statistics course in 2015–2016 academic years. Every class size ranged from 41 to 57 students. A Spearman’s correlation analysis was adopted to examine the relationship. A preliminary study on the data shows that there are seven factors contributing to students’ attitude toward elementary statistics course. Students’ perception on their selfachievement in mathematics and their attitude toward statistics course are related to each other. This study found that students with a good mathematics achievement tend to have a more positive attitude toward statistics